FTIR, GC-MS Analysis and Bioactivity Studies of Withania somnifera L. of Nepalese Origin - Aryal, Sangam; Shrestha, Sunita; Devkota, Anil; Bhandari, Netra Lal; Jha, Ram Narayan (Journal of Nepal Chemical Society, 2020)
Present study evaluates the bio-constituents and bioactivity of extract from roots and stems of Withania somnifera (Aswagandha) of Nepalese origin. The phytochemical screening of methanol and n-hexane extracts revealed the presence of alkaloids, flavonoids, phenols, tannins, quinone, carbohydrates, resins, xanthoprotein etc. The FTIR analysis helped to confirm the functional groups of various medicinally important compounds. The DPPH percentage radical scavenging activity of methanolic and hexane extracts are found to be 3.587 ± 0.004, and 4.484 ± 0.003 µg/mL respectively. The antioxidant activity of the plant goes after the number of total phenolics and flavonoids present on it. GC-MS analysis revealed the presence of more than 14 different compounds in the extract. Moreover, the methanol and hexane extract of plant showed 25.8% and 12.9% α-glucosidase inhibitory activity respectively. The results of the study revealed the medicinal values and pharmacological significance of the plant.